(111) TiO2-x/Ti3C2: Synergy of active facets, interfacial charge transfer and Ti3+ doping for enhance photocatalytic activity. (May 2017) - Peng, Chao; Wang, Hongjuan; Yu, Hao; Peng, Feng
Graphical abstract: Highlights: Two-dimensional (2D) transition metal carbide Ti3 C2 and a novel Ti 3+ doped rutile TiO2 /Ti3 C2 composite was firstly fabricated. The high active (111) facets of TiO2 was adjusted by the concentration of NH4 F. The percentage of Ti3 C2 in composites was adjusted by hydrothermal duration. The Ti3 C2 for separating charges and Ti 3+ dopant for narrowing band gap, the composite exhibited excellent photocatalytic activity under visible light. Abstract: The rational design of interface is a key factor for improving the performance of photocatalysts. Herein, a nanocomposite comprised of Ti 3+ doped rutile TiO2 octahedrons exposing active (111) facets and two-dimensional Ti3 C2 sheets was synthesized by a hydrothermal oxidation route and subsequent hydrazine hydrate reduction. The crystallographic facet proportions of TiO2 can be controlled by NH4 F as a facet controlling agent. The photocatalytic activity of the TiO2 /Ti3 C2 composite was maximized by completely exposing the active (111) surfaces. The interfacial microstructure between Ti3 C2 and TiO2 can be tuned by the hydrothermal reaction duration. The charge kinetics was substantially steered by the hole trapping effect of 2D Ti3 C2 terminated by OH groups. Through the reduction by hydrazine hydrate, Ti 3+ was doped into the bulk of TiO2, thereby enabling the photocatalytic activity under visible light. This work opens a new window to the rational design of photocatalysts based on 2D MXene materials.